A hard pill to swallow? Parental health shocks and children's mental health - Felix Glaser; Gerald J. Pruckner (Johannes Kepler University of Linz, Department of Economics, 2022)
Based on comprehensive administrative health record data from Austria, this study examines how children's mental health responds to a severe parental health shock. To account for the endogeneity of a serious parental illness, our sample is restricted to children who experience the health shock of a parent at some point in time and we exploit the timing of shocks in a dynamic DID setting. We find a positive causal effect of parental health shocks on children's mental health care utilization. Affected children have higher medical attendance for the treatment of mental illnesses, consume more psychotropic drugs, and are more likely to be hospitalized with mental and behavioral disorders. A significant increase in the utilization of antidepressants, anxiolytics, and sedatives can be observed for older children, girls and children with a white-collar family background. Our findings have important policy implications for children's access to psychotherapies and mental health care after experiencing a traumatic household event.
Keywords: I10; I12; I14; I31; 330; Mental health of children; parental health shock; difference-in-differences